(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
In this article we evaluate the ecological impressions of carbon capture and use (CCU) and carbon capture and storage (CCS) of technologies. To this end research on the assessment of the life cycle from the different literatures has been addressed. There are a total of 27 reports, 11 on CCS and 16 on CCU. CCS research has shown that power plants will reduce their global warming potential (GWP) from 63 to 82 percent, with combustion of oxygen fuel in pulverized coal and integrated combined cycle gasification (IPCG) plants to the greatest reduction and post-combustion capture in combined-cycle gas turbine (CCGT) plants, achieving the least reductions. CCS has higher environmental impacts than without acidification and human toxicity. The GWP for CCU varies greatly depending on how it is used. Mineral carbonation will decrease GWP by 4% to 48% compared to no CCU. In addition, compared to conventional DMC techniques, under CO2 lowers the GWP by 4.3 times and ozone depletion by 13 times for chemical extraction.